Etiopia pomiędzy oralnością a piśmiennością - Wołk-Sore, Ewa (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
This article is an attempt at applying the theory of orality/literacy, which was formulated by Milman Parry and Albert B. Lord and developed further by Eric A. Haverlock, Walter J. Ong, Jack Goody and others, to the process of the transition from orality to literacy in Ethiopia – an old African state where the spoken and written word co-existed for over two thousand years, without one dominating the other. This paper makes a careful examination of that what was spoken and what was written in Ethiopia and how this may shed new light on the theory of orality/literacy.
Keywords: oralność; piśmienność; Etiopia